Quantification of acidity of table olives produced in the region south of Minas Gerais state - Medeiros, Rosalina Marangon Lima; Silva, Daniel Fernandes; Villa, Fabiola; Fernandes, Fabio Luiz Figueiredo (Agrarian, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 21 false false false <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> Although Brazil is one of the world's largest consumers of olives and olive oil, all of these products in the Brazilian market is derived from imported mainly from European countries. The olive is also a recent activity and in frank expansion in Brazil. Considering that the Brazilian soils and climate conditions are very different countries traditional the cultivation of olives, it is necessary the creation or adaptation of technologies for exploitation of this activity in the country. This study aimed to evaluate the quality of five varieties of canned olives prepared so natural by evaluating the acidity of the samples in different periods after preparation. The experiment was conducted at the Experimental Farm EPAMIG in Maria da Fé, Southern Minas Gerais State, Brazil, and the evaluations were performed at the Laboratory of Food Technology and Food Science of Fundação de Ensino e Pesquisa de Itajubá (FEPI). The treatments consisted of cotton cultivars, with and without the use of NaOH and brine 7%, with or without bleaching, sea salt to 7%, coarse salt 7%, to rest in brine at 5%, 7% and 9%, restless in brine at 5%, 7% and 9%. The treatments without bleaching, with NaOH and without rest independent of salt concentration are best used for the production of table olives had a lower acidity.